Rumen ciliates in Brazilian sheep (Ovis aries), with new records and redescription of Entodinium contractum (Entodiniomorphida: Ophryoscolecidae) - Cedrola, Franciane; Martinele, Isabel; Dias, Roberto Júnio Pedroso; Fregulia, Priscila; D’agosto, Marta (Zootaxa, 2016)
The species composition, prevalence, and average relative abundance of rumen ciliates were analyzed in 16 Brazilian sheep. 28 species of ciliates were identified belonging to 3 families: Isotrichidae, Ophryoscolecidae, and Parentodiniidae. Among these ciliates, Entodinium alces, Metadinium esalqum, and M. rotundatum were found for the first time in sheep, and other 12 species for the first time in Brazilian sheep. Different morphotypes of parentodiniid ciliates were identified in 7 of the 16 sheep analyzed and this is the second report of this family in ruminants. The species Entodinium contractum was redescribed based on the new data on the general morphological features; for the first time, we described the oral infraciliature, which in this species is of the Entodinium-type. In this species, it is noteworthy that the prominent vestibular polybrachykinety can be used as an important identifying characteristic.